2018
DOI: 10.4103/ijnmr.ijnmr_198_16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition education in improving dietary pattern during pregnancy based on pender's health promotion model: A randomized clinical trial

Abstract: Background:Different types of nutrients in adequate amounts are required to meet the increased demands of the mother and the developing fetus. Therefore, we examined the impact of nutrition education on the number of food servings per day.Materials and Methods:Pregnant mothers were recruited to a prospective, randomized clinical trial from May to September, 2016. At 6–10 weeks of gestation, the participants were randomly divided into the intervention (n = 96) or the control group (n = 96), and were followed-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
26
1
3
Order By: Relevance
“…The indirect effect through path1 (intervention effect through dietary practice) was significant. Previous studies also reported the positive effect of nutrition counseling in improving the dietary practice of pregnant women [ 52 , 56 ] which, in turn, improved birth weight [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
“…The indirect effect through path1 (intervention effect through dietary practice) was significant. Previous studies also reported the positive effect of nutrition counseling in improving the dietary practice of pregnant women [ 52 , 56 ] which, in turn, improved birth weight [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
“…Kontrol grubunda ise acil rekabetçi talepler ile sebze tüketimi arasında negatif ilişki bulunmuştur. 24 Bu çalışmada, eş desteğinin davranış değişiminde etkili olduğu saptanmıştır. Çalışmamızda da, olgunun eşinin diyet ve fiziksel aktivite yaparak destek olması davranış değişiminde etkili olmuş ve acil rekabetçi talep olarak ara öğünlerde meyve veya yoğurt yemeyi tercih etmiştir.…”
Section: Discussionunclassified
“…The Health Promotion Model identifies factors that influence health behaviors. Pender’s Health Promotion Model is one of the most widely used models to identify and change unhealthy behaviors and promote health [ 10 , 11 ]. Predicting factors and explanatory constructs of health behavior in Pender’s model include perceived benefits, barriers, and self-efficacy; behavioral emotions; and interpersonal and situational influencers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pender’s Health Promotion Model has been widely adopted to explore different health promotion behaviors [ 10 , 11 , 19 ] and has achieved concrete results. However, limited studies have utilized this model to investigate older adults’ engagement in community-based health promotion activities.…”
Section: Introductionmentioning
confidence: 99%